A tribute to Marty Taubman: the Earl of Sandwich, IgA, T-regs, and the Celtics - Genco, R J (Journal of dental research, 2014)
This tribute to Marty Taubman is written on the occasion of his retirement from full-time faculty status at The Forsyth Institute and Harvard Dental School, and his stepping down as editor of the "Discovery!" section of the Journal of Dental Research. It recognizes his seminal contributions to oral immunology, his mentoring of a generation of new scientists, his key role as a leader in organized research as president of the American Association for Dental Research, as well as his editorship, which has recognized scores of his colleagues in science. He is a leader in our field and has made many lasting contributions to research, teaching, and our profession, for which we are very grateful.